Social class and social structure in a middle-sized Pennsylvania community - Lowis, George W. (The Greek Review of Social Research, 1972)
The major purpose of this study is to describe select demographic and socio-cultural characteristics associated with the five social classes of the social structure in an urban Pennsylvania community. Classes are delineated by the Hollingshead Index of Social Position. Description of the class characteristics is made more fruitful through use of this index. The stratification procedure demonstrates that stratifying a population enables us to better understand the organization and function of a community as a sociological entity.